2008
DOI: 10.1016/j.ajhg.2008.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Evolution of UGT2B17 Copy-Number Variation

Abstract: The human UGT2B17 gene varies in copy number from zero to two per individual and also differs in mean number between populations from Africa, Europe, and East Asia. We show that such a high degree of geographical variation is unusual and investigate its evolutionary history. This required first reinterpreting the reference sequence in this region of the genome, which is misassembled from the two different alleles separated by an artifactual gap. A corrected assembly identifies the polymorphism as a 117 kb dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
140
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(154 citation statements)
references
References 56 publications
8
140
1
4
Order By: Relevance
“…Conrad et al 2010). A number of studies have detected candidate CNVs under selection by examining allele frequency differentiation between populations (Redon et al 2006;Perry et al 2007;Xue et al 2008;Conrad et al 2010) or by examining differentiation at the ends of a cline (Turner et al 2008b). For example, Perry et al (2007) found that the number of copies of the human salivary amylase gene, AMY1, is typically higher in populations with high-starch diets than in those with low-starch diets, and that this difference is probably due to adaptive natural selection.…”
Section: Evidence For Natural Selection On Cnvsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conrad et al 2010). A number of studies have detected candidate CNVs under selection by examining allele frequency differentiation between populations (Redon et al 2006;Perry et al 2007;Xue et al 2008;Conrad et al 2010) or by examining differentiation at the ends of a cline (Turner et al 2008b). For example, Perry et al (2007) found that the number of copies of the human salivary amylase gene, AMY1, is typically higher in populations with high-starch diets than in those with low-starch diets, and that this difference is probably due to adaptive natural selection.…”
Section: Evidence For Natural Selection On Cnvsmentioning
confidence: 99%
“…For example, Perry et al (2007) found that the number of copies of the human salivary amylase gene, AMY1, is typically higher in populations with high-starch diets than in those with low-starch diets, and that this difference is probably due to adaptive natural selection. Another example comes from the human UGT2B17 gene, the enzyme product of which metabolizes steroids and foreign compounds, and has a polymorphic deletion that may be experiencing balancing selection in Europeans and positive selection in East Asians (Xue et al 2008); the deletion allele has been associated with several phenotypes that are the possible targets of selection (Xue et al 2008).…”
Section: Evidence For Natural Selection On Cnvsmentioning
confidence: 99%
“…Thus, de novo generation of CNVs to an individual's genome seems to be 100 times less common than the contribution of inherited CNVs [13]. Furthermore, it also seems that there is a substantial inter-population variation of CNVs among human populations [5,[14][15][16]. For example the CCL3L1 gene, which encodes a potent human immunodeficiency virus (HIV)-1-suppressive chemokine, shows striking geographical structuring among human populations, indicating that variability in copy number has probably contributed to adaptation to different environmental conditions [16].…”
mentioning
confidence: 99%
“…39,42,43 The deletion gene polymorphism has high frequency in East Asian, intermediate frequency in European/West Asian and low frequency in African population. 44 UGT 2B17 gene polymorphism contributes to ethnic differences in androgen glucuronide levels. However, the exact role of the differences in androgen glucuronidation in the suppression of spermatogenesis has not been studied directly.…”
Section: Differences In Hormone Concentrations and Metabolismmentioning
confidence: 99%